PENGARUH KUALITAS PRODUK DAN KUALITAS PELAYANAN TERHADAP LOYALITAS PELANGGAN PADA OPERATOR SELULER XL AXIATA - Resa Nurlaela Anwar; Raynes Firdaus (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2021)
The purpose of this study was to determine the effect of customer loyalty on users of XLinternet data provider. This research was conducted using a data collection method by meansof a questionnaire on 100 users of the XL internet provider data package. Samples were takenwith non-probability in the form of purposive sampling. Testing the quality of the data in thisstudy used validity and reliability tests. Data were analyzed using simple linear regressionanalysis and multiple linear regression, classical assumption tests (normality test,multicollinearity test, autocorrelation test, and heteroscedasticity test) were performed asstatistical requirements that must be met in performing linear regression analysis (simpleand multiple). Simultaneous hypothesis testing using the F test, partially using the T test. Theresults showed that there was a significant influence between the variables of ProductQuality and Service Quality on Customer Loyalty with a significance probability of 0.000<0.05. For the Product Quality variable on Customer Loyalty, it shows an insignificantnegative effect with a significance probability of 0.734 > 0.05 and for the Service Qualityvariable on Customer Loyalty it shows a significant positive effect with a significanceprobability of 0.010 < 0.05.